2016
DOI: 10.7150/ijbs.13805
|View full text |Cite
|
Sign up to set email alerts
|

A Group of Novel Serum Diagnostic Biomarkers for Multidrug-Resistant Tuberculosis by iTRAQ-2D LC-MS/MS and Solexa Sequencing

Abstract: The epidemic of pulmonary tuberculosis (TB), especially multidrug-resistance tuberculosis (MDR-TB) presented a major challenge for TB treatment today. We performed iTRAQ labeling coupled with two-dimensional liquid chromatography-tandem mass spectrometry (2D LC-MS/MS) and Solexa sequencing among MDR-TB patients, drug-sensitive tuberculosis (DS-TB) patients, and healthy controls. A total of 50 differentially expressed proteins and 43 differentially expressed miRNAs (fold change >1.50 or <0.60, P<0.05) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…Other recent biomarker studies have identified additional miRNA that may have biomarker potential to aid TB diagnosis. miRs-144, -223, -29a, -155 and 424 have all been reported as providing AUC over 0.8 or sensitivity and specificity over 80% as a single miRNA biomarker aiding TB diagnosis (12,(22)(23)(24)(25). Of these, only miRs -223 and -29a were significantly regulated in our exploratory study, with only miR-29a remaining significantly regulated in the validation study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent biomarker studies have identified additional miRNA that may have biomarker potential to aid TB diagnosis. miRs-144, -223, -29a, -155 and 424 have all been reported as providing AUC over 0.8 or sensitivity and specificity over 80% as a single miRNA biomarker aiding TB diagnosis (12,(22)(23)(24)(25). Of these, only miRs -223 and -29a were significantly regulated in our exploratory study, with only miR-29a remaining significantly regulated in the validation study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(9,10). Studies have shown changes in blood miRNA levels in small numbers of patients with active TB that have biomarker potential (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA): Cheng et al, 140 Dwivedi et al, 141 Ortea et al, 142 Serada and Naka, 143 135 Wang et al, 136 Xu et al, 137 Considering the influence of cerebrovascular irregularities, the plasma proteomics of acute ischemic stroke 123 has been studied. Also regarding a subtype of the latter, that is, lacunar infraction, Datta et al enriched mircovesicles from plasma to determine whether differences in their proteomic profiles could be used to predict adverse outcome in the surviving patients.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…134 Although cord blood serum can be richer in intracellular proteins and more varied than matured serum, the study was conducted with older MS instrumentation (Applied Biosystems, QSTAR-Pulsar) and they reported quantification of in the order of 200 proteins. Other studies of respiratory afflictions have included tuberculosis [135][136][137][138] and Mycoplasma pneumoniae (MP) infections 139 (see below). Examples of these applications are indicated in Table 5A.…”
Section: Respiratory Illnessesmentioning
confidence: 99%
See 1 more Smart Citation